Pengaruh Pengaruh Likuiditas Dan Leverage Terhadap Profitabilitas Pada PT. Gudang Garam Tbk (Tahun 2016 – 2020): Likuiditas, Leverage, Profitabilitas - Dian, Corrina; Dwi, Erika; Khoirun, Bella; Wahyu, Yahya; Ermayanti, Dwi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
This study hopes to check the resultant liquidity and leverage on profitability. The analytical method used is a quantitative regulation which is found to be additionally investigated by non-participation or indirectly, in particular by collecting, presenting and researching secondary evidence in the form of financial complaints of PT. Gudang Garam Tbk 2016 - 2020. The results of the uniformity check of the Kolmogorov-Smirnov checks that were carried out showed that the causes used in the analysis were based on a basic distribution plus a perception period of 0.079 (more designs sourced 0.05). In this unit, the profit of PT Gudang Garam Tbk in 2016 - 2020 is influenced by the constituents of liquidity and leverage.